2002
DOI: 10.1046/j.1365-2486.2002.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

An initial intercomparison of micrometeorological and ecological inventory estimates of carbon exchange in a mid‐latitude deciduous forest

Abstract: The role of mid‐latitude forests in the sequestration of carbon (C) is of interest to an increasing number of scientists and policy‐makers alike. Net CO2 exchange can be estimated on an annual basis, using eddy‐covariance techniques or from ecological inventories of C fluxes to and from a forest. Here we present an intercomparison of annual estimates of C exchange in a mixed hardwood forest in the Morgan‐Monroe State Forest, Indiana, USA for two years, 1998 and 1999. Based on eddy‐covariance measurements made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 39 publications
4
85
1
1
Order By: Relevance
“…From these definitions, the NEP was regarded as the net carbon budget of ecosystems (NRCB). For natural ecosystems, which had no strong natural and anthropogenic disturbances, previous studies showed that the NEP obtained by the biomass inventory method and eddy covariance method agreed well with each other [80][81][82]. However, for ecosystems strongly affected by human activities at a regional scale (biomesociety system), especially at a long-term scale, anthropogenic and natural disturbances still exist, including food collection, timber harvesting, burning of plant residues, fires, water erosion and other geological processes that cause carbon leakage.…”
Section: Carbon Budget Components Of Terrestrial Ecosystems In Chinamentioning
confidence: 65%
“…From these definitions, the NEP was regarded as the net carbon budget of ecosystems (NRCB). For natural ecosystems, which had no strong natural and anthropogenic disturbances, previous studies showed that the NEP obtained by the biomass inventory method and eddy covariance method agreed well with each other [80][81][82]. However, for ecosystems strongly affected by human activities at a regional scale (biomesociety system), especially at a long-term scale, anthropogenic and natural disturbances still exist, including food collection, timber harvesting, burning of plant residues, fires, water erosion and other geological processes that cause carbon leakage.…”
Section: Carbon Budget Components Of Terrestrial Ecosystems In Chinamentioning
confidence: 65%
“…In a study performed in five North American deciduous forests (Curtis et al, 2002), such discrepancies were observed between NEE and BI, with the largest difference being 220 g C m −2 y −1 . In a North American mixed deciduous forest, Ehman et al (2002) reported estimates of carbon uptake from inventories to be 34 and 90 g C m −2 y −1 higher for two successive years, than from eddy covariance measurements. In a mixed hardwood forest, both estimates agreed within 5% (Schmid et al, 2000).…”
Section: Tree Biomass Increment and Delayed Effects Of Droughtmentioning
confidence: 91%
“…In southern pine forests, most of the belowground biomass is in coarse roots Laiho and Finer 1996;Johnsen et al 2001). Coarse-root and stump biomass has been found to increase with the age of the stand, constituting up to 90% of the total living root biomass (Laiho and Finer 1996;Ehman et al 2002). Following harvest or natural tree mortality, root systems become a ''source'' of carbon as they decay in a negative exponential Carbon content of root systems is estimated at the time of harvest, representing the maximum amount of C in decomposing roots pattern over decades, releasing CO 2 to the atmosphere.…”
Section: Discussionmentioning
confidence: 99%